Spectacle correction of anisometropia following cataract surgery - Nogaj, Sławomir; Dubas, Katarzyna; Michalski, Andrzej; Stopa, Marcin (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Optical correction after cataract surgery is an important issue, especially after intraoperative complications or experiencing refractive prediction error. Patients with these issues often have anisometropia and symptoms of aniseikonia. Also, optical anisophoria should be carefully corrected in these cases. Here we discuss and analyze the most common clinical situations which clinicians can encounter and outline the individual approach in each scenario.